2019
DOI: 10.1021/acs.chemmater.9b00086
|View full text |Cite
|
Sign up to set email alerts
|

InP/ZnS Quantum Dots as Efficient Visible-Light Photocatalysts for Redox and Carbon–Carbon Coupling Reactions

Abstract: Scheme 1. Schematics Showing the Potency of InP/ZnS QD to Photocatalyze Two Distinctly Different Reactions: Metal-Centered Ferricyanide Reduction and C−C Bond Formation between PhPyr and PhSO 2 a a InP/ZnS QD photocatalyzed the ferricyanide reduction in the presence of a sacrificial reagent, ethanol, with high photoconversion yield and recyclability (left side). Strikingly, InP/ZnS QD was able to photocatalyze the C−C coupling reaction exclusively without the aid of any cocatalysts or sacrificial reagents (rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 51 publications
1
86
0
Order By: Relevance
“…Colloidal quantum-conned nanocrystals, especially spherical quantum dots (QDs), can exhibit a broad tunability of their band-gaps, multiexciton lifetimes and band-edge positions by simply varying the particle sizes, 1,2 enabling their applications in lasing, 3,4 light-emitting diodes (LEDs), [5][6][7] and solar fuel generation. [8][9][10][11] In the past few decades, Cd and Pb-based chalcogenide nanocrystals (e.g., CdSe 3,4 and PbSe 12 ) have been widely investigated, leading to signicant advancement of our fundamental understanding of exciton and carrier dynamics of QDs and how these properties can be optimized through size, shape and composition control of QDs and heterostructures to improve their device performances. 2,13,14 However, the toxic heavy metals in Cd-and Pb-based QDs pose potential human health risks, hindering their commercial applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colloidal quantum-conned nanocrystals, especially spherical quantum dots (QDs), can exhibit a broad tunability of their band-gaps, multiexciton lifetimes and band-edge positions by simply varying the particle sizes, 1,2 enabling their applications in lasing, 3,4 light-emitting diodes (LEDs), [5][6][7] and solar fuel generation. [8][9][10][11] In the past few decades, Cd and Pb-based chalcogenide nanocrystals (e.g., CdSe 3,4 and PbSe 12 ) have been widely investigated, leading to signicant advancement of our fundamental understanding of exciton and carrier dynamics of QDs and how these properties can be optimized through size, shape and composition control of QDs and heterostructures to improve their device performances. 2,13,14 However, the toxic heavy metals in Cd-and Pb-based QDs pose potential human health risks, hindering their commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…With a bulk bandgap at 1.35 eV and suitable bandedge energies (CB: À3.85 eV and VB: À5.2 eV), 15 InP QDs can be tuned to absorb a wide range of photoenergies and see emerging applications in solar cells, 16,17 LEDs, 7,18 and photocatalytic reactions. 8,10 However, despite the desirable material properties, early studies 19,20 have shown that these materials contain a large density of traps states (Scheme 1a), evidenced by their low photoluminescence (PL) quantum efficiencies. Two postsynthetic methods have been developed to passivate the trap states in InP QDs and improve their PLQEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Pillai's group also showed the efficient photocatalytic ability of InP/ZnS QDs through two different classes of redox reactions as metal‐centered and C−C bond formation . By tuning the surface ligands, InP/ZnS QD could enable different photocatalytic reaction in aqueous solution as well as in organic media.…”
Section: Cd‐free Qds For Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…Later, Pillai's group also showed the efficient photocatalytic ability of InP/ZnS QDs through two different classes of redox reactions as metal-centered and CÀ C bond formation. [121] By tuning the surface ligands, InP/ZnS QD could enable different photocatalytic reaction in aqueous solution as well as in organic media. The excellent overlap of the efficiency in different wavelength and the absorption spectra confirmed the active participation of QDs in photocatalysis, further demonstrated the potential of InP QDs for photocatalytic application.…”
Section: Iii-vi Qds Photocatalystmentioning
confidence: 99%